Proportional integral sliding mode control of a two-wheeled balancing robot [compact disc] - 423217 Mohd. Fairus Abdollah (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2006